2010
DOI: 10.4236/jbpc.2010.11004
|View full text |Cite
|
Sign up to set email alerts
|

Mode of pollen spread in clonal seed orchard of Pinus koraiensis

Abstract: The patterns of effective pollen dispersal and the relationships between pollen dispersal and genetic composition in Pinus koraiensis are still unclear. Hence, we investigated the mode of pollen dispersal of P. koraiensis in a clonal seed orchard in Lushuihe Forestry Bureau, Jilin Province, using SSR molecular markers tech-nique and the method of maximum likelihood. A total of 13 pairs of nuclear microsatellites po-lymorphic primers were used in the paternity analysis. We analyzed 100 progenies and 150 paterni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…However, the values determined in this study were higher compared to results reported by [ 76 , 77 ], which analyzed the mating system in a complete P. koraiensis population containing seeds, male and female trees using 14 SSR markers. Our results corroborated previous studies [ 78 , 79 ], which indicated higher genetic diversity in Chinese natural Korean pine populations compared to that of other populations in the Russian region.…”
Section: Discussionsupporting
confidence: 93%
“…However, the values determined in this study were higher compared to results reported by [ 76 , 77 ], which analyzed the mating system in a complete P. koraiensis population containing seeds, male and female trees using 14 SSR markers. Our results corroborated previous studies [ 78 , 79 ], which indicated higher genetic diversity in Chinese natural Korean pine populations compared to that of other populations in the Russian region.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, for P. koraiensis, the level of genetic diversity in this study was higher than that in previous reports employing other means of detection, such as allozymes (H e = 0.183) [2], RAPD molecular markers (H e = 0.169) [20], and ISSR molecular markers (H e = 0.601) [3]. These differences may be due to the different numbers and types of genetic detection technologies used in the studies or to the different populations and biased sample sizes.…”
Section: Genetic Diversitycontrasting
confidence: 74%
“…et Zucc., also known as Korean pine, is an evergreen tree belonging to the Pinus genus and Pinaceae family [1]. It is mainly distributed in the mountainous area of Northeast China, as well as in North Korea, Japan, and Far Eastern region of Russia [1][2][3]. P. koraiensis plays a key ecological role as the most important component of natural broad-leaved Korean pine forests, and it is also famous for its economic value, such as the production of good quality timber and edible seeds [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of Korean pine dates back more than a half century [7]. To date, significant gains have been realized, and several studies reported some improvements in growth rate, and seed and wood quality [8][9][10][11]. Facing multiple needs and a permanent global change, multi-objective approaches have been suggested for the sustainable management of forest resources [12].…”
Section: Introductionmentioning
confidence: 99%